Estudos dos mecanismos de resistência de genótipos de algodão submetidos à diferentes condições bióticas e abióticas - Pereira, Erika Thalyta Veras (2022)
Cotton is a cultivar of economic interest, with a worldwide turnover around 17 billion dollars per year. Its supply is marked by several interconnected factors such as market signals, climatic aspects and pest pressures. The Spodoptera complex is among the main pests of cotton plantations, and its control has economic interest. Thus, this work proposes to investigate the defense responses of different cotton genotypes and compare their chemical profile when subjected to different resistance inducing factors, thus contributing to the development of proposals and policies for sustainable agricultural management to control pest insects. Twelve cotton genotypes were studied, by comparing their chemical profile when subjected to herbivory by Spodoptera cosmioides. The FMT 701 and Delta Opal genotypes were submitted to six resistance induction treatments: application of methyl jasmonate solution on the soil at concentrations of 20 µmolL-1 and 200 µmolL-1, application by spraying methyl jasmonate on the leaves at a concentration of 200 µmolL-1, herbivory by S. cosmioides, herbivory by S. cosmioides and application of methyl jasmonate (200 µmolL-1) in the soil, and water deficit stress. GC-MS and UPLC-QTof-MS analysis methodologies were developed, optimized and validated. Compounds such as α-tocopherol, p-coumaric acid, 1-linoleoylglycerol, 2-monopalmitin, campesterol and heliothrin were identified as metabolites associated to the defense response of genotypes to herbivory. The exogenous application of methyl jasmonate to Delta Opal and FMT 701 genotypes was more effective when sprayed on leaves. No accumulation of methyl jasmonate was identified in the experiments of exogenous application, but there was a change in the metabolomic profile, that is, the application of methyl jasmonate does not cause its accumulation but induces changes in the metabolism of the genotypes. A positive correlation was observed between the addition of methyl jasmonate and the accumulation of linolenic acid, linoleic acid and jasmonic acid in Delta Opal and FMT 701, and these compounds are already known as signal defense responses in plants. The Delta Opal and FMT 701 cultivars did not respond metabolically to water stress. It can be concluded that the cotton defense mechanism encompasses different metabolites from different routes and no single substance is responsible for the plant's defense.